5-(2x-3)=-3+6

Simple and best practice solution for 5-(2x-3)=-3+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-(2x-3)=-3+6 equation:


Simplifying
5 + -1(2x + -3) = -3 + 6

Reorder the terms:
5 + -1(-3 + 2x) = -3 + 6
5 + (-3 * -1 + 2x * -1) = -3 + 6
5 + (3 + -2x) = -3 + 6

Combine like terms: 5 + 3 = 8
8 + -2x = -3 + 6

Combine like terms: -3 + 6 = 3
8 + -2x = 3

Solving
8 + -2x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -2x = 3 + -8

Combine like terms: 8 + -8 = 0
0 + -2x = 3 + -8
-2x = 3 + -8

Combine like terms: 3 + -8 = -5
-2x = -5

Divide each side by '-2'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| 9/30 | | 183-2m=4m | | 4X-3/5=X+3/10 | | X^2-10x+7=3 | | 135+4m=13m | | 7/8=5/8+9 | | 4X-3/5 | | 8m+78=11m | | 5-x+3x=29 | | 7-6(5y-y)=10(y-4) | | 12m=7m+205 | | -4c=28 | | 6(4X+5)+7=2 | | 175000+550x=35000+1680z | | 12.00+(-2.00x)=10 | | 5+(-2)+3x=9 | | 4(2m-4)=5(m+4) | | 5n+7-8n=2.5 | | 2XY+4AY-3BX= | | 26x^2-30x-25=0 | | 6x=2x+70 | | y=-2x^2-7x | | 5y-5+y+21=5y+20-3y | | 26x^2-30x-26=0 | | (5x+3)-(2x-8)= | | 5(3x+8)-3(4x-7)=0 | | -4-y=7y-36 | | k/3+5=6 | | y=2x^2-7x | | 76-6m=6m-104 | | (n^2v-10n+24)/(n^2-13n-20)-(9)/(n-7) | | 3x+(-9)/(-3)=24 |

Equations solver categories